Analysis Strategy in the Department Store Changes Facing Lifestyle on Consumer New Era of Normal - Ni Kadek Santi Oktaviani Anggreanti; I GustiNgurah Putra Suryanata (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
This study aimed to find out how the formulation of the right strategy in the face of lifestyle changesconsumer in a normal new era where the era of disruption which is a change that occurs due to the development of information technology applications and causes changes in lifestyle patterns, especially in terms of shopping (shopping lifestyle). Trend consumers and lifestyles of today are constantly changing. This forces entrepreneurs to continue to innovate, by going ahead of consumers and dictating the lifestyle of consumers themselves, or following existing trends. This research was conducted in a department store in Bali using a qualitative descriptive method. The technique used in selecting informants is purposive sampling technique. The data collection techniques used were observation, in-depth interviews, and documentation, with the data validation method using triangulation. The results of this study indicate that 1) internal factors of Matahari Duta Plaza in terms of strength are human resources (HR) who have the ability to produce knowledge, quality products, and friendly prices, in terms of weaknesses, namely the location with minimal parking. 2) External factors of Matahari Duta Plaza in terms of opportunities for technological developments to facilitate transactions, in terms of threats, namely increasingly fierce industrial competition.